2022
DOI: 10.3168/jds.2021-21539
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the cost of ketosis in dairy cattle

Abstract: A systematic review was conducted to assess the cost of ketosis in dairy cattle, and to elucidate how ketosis cost is estimated in each of the studies. Scientific papers addressing the economic impact of ketosis in dairy cows were identified through a search in 4 databases (Medline, ISI Web of Science, CAB Abstracts, and Agricola). The literature search was conducted with no restrictions on the date of study publication, publication type, or language. The methodological quality of the studies was assessed rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…During the perinatal period of dairy cows, the body will undergo complex physiological changes, among which ketosis often occurs [24]. The occurrence of ketosis is often accompanied by fat deposition in the liver [25]. The essence is that after excess NEFAs (nonesterified fatty acid, fatty acids above C10, mainly VLCFAs) enter the liver, part of NEFAs enter the ketone body synthesis pathway to generate ketone bodies [26,27].…”
Section: The Significance Of Peroxisomal β-Oxidationmentioning
confidence: 99%
“…During the perinatal period of dairy cows, the body will undergo complex physiological changes, among which ketosis often occurs [24]. The occurrence of ketosis is often accompanied by fat deposition in the liver [25]. The essence is that after excess NEFAs (nonesterified fatty acid, fatty acids above C10, mainly VLCFAs) enter the liver, part of NEFAs enter the ketone body synthesis pathway to generate ketone bodies [26,27].…”
Section: The Significance Of Peroxisomal β-Oxidationmentioning
confidence: 99%
“…El tratamiento con propilenglicol por vía oral mejora el estado de saludde los animales (Serrenho et al, 2022). El costo del tratamiento de la cetosis bovina es muy variable de una fuente a otra, con montos de tratamiento individual que varían desde los 19€ hasta los 812€, o en otros casos con costos a nivel de granja de 3,6-29 €/vaca/año, lo que significa que la cetosis tiene un impacto económico general considerable en el ganado lechero (Cainzos et al, 2022).…”
Section: Figura 21unclassified
“…The prevalence of subclinical ketosis is higher than that of clinical ketosis in lactating dairy herds [ 14 , 15 ]. Evaluations of economic loss indicate that ketosis is not the main factor affecting milk production but it increases the risk of other diseases and culling [ 16 , 17 ]. Sordillo et al [ 18 ] and Pascottini et al [ 19 ] have reported significant negative effects caused by the inflammatory response to ketosis.…”
Section: Introductionmentioning
confidence: 99%